Vitamin D Deficiency in Patients with First Episode of Acute Coronary Syndrome (Medical Forum Monthly, 2024)
Objective: To determine the frequency of Vitamin D deficiency in acute coronary syndrome patients. Study Design: Cross Sectional Study. Place and Duration of Study: This study was conducted at the Department of Cardiology ward or Coronary care unit (CCU) at Liaquat National Hospital and Medical College, Karachi from October 2018 and April 2019. Materials and Methods: This single center, non probability consecutive, cross sectional study was conducted from 6th October 2018 and 5th April 2019. A total of 159 patients presented first time with acute coronary syndrome were incorporated in this research. A thorough examination and detailed history of all the systems, especially examination of cardiovascular system and abdomen was done. 5 cc bloods was taken from the prominent peripheral vein and collected. Blood sample was shifted to the laboratory within 30 minutes from the time of withdrawn for the measurement of 25 Hydroxyvitamin D level. Pre-designed proforma was used to collect and document data. Results: There were 109(68.55%) male and 50(31.45%) female. Frequency of deficiency of vitamin D in patients with first episode of acute coronary syndrome (ACS) was observed in 74.21% (118/159). Conclusion: There were 109(68.55%) male and 50(31.45%) female. Frequency of deficiency of vitamin D in patients with first episode of acute coronary syndrome (ACS) was observed in 74.21% (118/159).